Comparison of individual penalties according to gender and weight categories of elite judo athletes from four world championships - Kajmovic, H.; Karpljuk, D.; Kapo, S.; Simenko, J. (Biology, 2022)
Simple Summary: Penalties in judo (shido) have been previously associated with match outcomes and increased the likelihood of being defeated, particularly in heavier weight categories. Each 1-min increase in match duration and further athlete proceeds in competition increases the possibility of receiving a penalty. Penalties have also been associated with the occurrence of injuries, especially with grip fighting and other illegal moves and therefore, have a substantial effect on athletes` health. The main findings highlighted that the leading penalties in all weight categories for both genders on Judo World Championships (WC) were Non-combativity, Avoid Grip and False Attack. Additionally, a new trend in heavyweight athletes with a lower number of penalties is noted.